of Prophets, Pagans and the Middle East (American Journal of Islam and Society, 2001)
The term “postmodernity” perhaps owes its very popularity to the fact thatit is notoriously difficult to define. It often means all things to all people,and by its very orientation, is critical of any attempts to offer blanketdefinitions. Nevertheless, we may discern three broad orientations thatdefine postmodernity:1. It involves an “incredulity toward metanarratives.”* In other words, itrepudiates the modernist view thd individual actions can be explainedthrough universal laws.2. It focuses on the crisis of repre~entation.I~n other words, it is critical ofthe power vested in any subjectivity to represent the reality of another.3. It problematizes the issue of subject and author? For example, it wouldquestion the claim made by this journal that it is a more ‘official’ interpreterof Islamic thought than some others: a claim this joumal may seek toadvance on the basis of its institutional power.This somewhat arbitrary set of attributes associated with postmodernitymay seem quite innocuous at first reading. But postmodernity (or its nowemerging normative arm, postmodernism) is evidently much more thanthat, as its adherents and critics have pointed out. It has been associatedwith a lot of other phenomena. For instance, in the economic realm, wehave the notion of post-Fordism, a situation where the precepts of massproduction are being overturned. Based on computer-aided manufacture, arapidly heterogenizing consumer demand, and the emergence ofnewer forms of commerce (such as Ecommerce over the internet), a newindustrial paradigm is emerging.5 At the same time, we have thephenomenon of post-nationalism, where the sovereignty of nations is beingthreatened by the emergence of supranational forms of governance suchas multinational corporations and the WT0.6 However, the issue that ...